Gorgias and Isocrates’ Grave - Gemin, Marco (Peitho. Examina Antiqua, 2018)
Gorgias, the teacher of Isocrates, is rarely mentioned in Isocrates’ works and never in a flattering way. He is also presented, among other masters and poets, on Isocrates’ grave in a way that appears to be consistent with his pupil’s thought. Thus, the author of the iconographic plan of the grave may have been either Isocrates himself or someone who sufficiently knew his works and properly understood his tempestuous relationship with his master.